La tentation du socialisme au Bénin - Genné, Marcelle (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1978)
The achievement of scientific socialism as conceived by MM. Ch. Bettelheim, J. Charrière and H. Marchisio is based on four general principles, namely : the taking of power by proletarian party ; the establishment of the dictatorship of the proletariat ; the public ownership and control of the economy ; and agricultural reform. Relating the experience of Benin to these fundamental principles shows that there are different paths to socialism. Accordingly, the accumulation of different facts leads to a revision of the theory of scientific socialism.